(untitled) (Journal of Organizational Psychology, 2024)
Current disruption era necessitates ongoing skill development for HR through training. Competency of professional trainers is key to training success. In-depth interviews with training managers, professional trainers, and training attendees revealed three components of competency - traits, knowledge, and skills. Traits comprised attitude (i.e., great heart and growth) and personality (i.e., passionate, accessibility, signature, and suitable to audience). Knowledge comprised expertise (i.e., content expertise and company/industry expertise) and experience (i.e., work experience and life experience). Skills comprised learning design skills (i.e., application of appropriate techniques and stakeholder-centered design), delivery skills (i.e., application-oriented and persuasive and inspiring), and developing business skills/entrepreneurship.